Effect of Physical Rotations and Gender for Navigation Performance in Virtual Environments - Kitson, Alexandra; Grechkin, Timofey Y.; Heyde, M. von der; Riecke, Bernhard E (International Meeting of the Psychonomic Society, 2016)
Physical motions may help orientation in virtual environments compared to only visual information. However, it remains unclear how much and what kind of motion is required to significantly increase orientation performance. In this study, we tested navigation performance in a virtual maze where participants (N=15) had to remember seven target objects and later point to them from different locations along the path. We compared two locomotion conditions: visual-only, where participants sat on a non-rotating chair and used the joystick for both forward movement and rotation; physical rotations, where participants sat on a swivel chair and controlled forward movement via joystick, while rotations were controlled by the Head Mounted Display’s gaze direction. Spatial orientation performance was quantified as pointing error, absolute ego-orientation error, and configuration error. Females showed larger difficulties in maintaining self-orientation (ego-orientation error) than males, F(1, 60) = 5.110, p = .027, η2 = .078, expanding prior research where gender differences are common in navigation studies. Unexpectedly, pointing consistency was better for the visual only condition, F(1, 60) = 5.160, p = .027, η2 = .079. Post-experimental debriefing suggests this lack of a benefit from physical rotation might be related to the inconsistency of using body movements only for rotations, but not translations. This suggests that embodied interfaces should include at least some physical translation or translational motion cueing, like the NaviChair we are currently developing based on these findings.
Keywords: Riecke; Riecke_2016; alex-kitson; bernhard-riecke; gyroxus; leaning-based interfaces; markus-von-der-heyde; motion cueing; motion-cueing; proj--motionCueingInterfaces; spatial updating; talkWithoutPaper; timofey-grechkin